The impact of cytomegalovirus infection on new-onset diabetesmellitus after kidney transplantation: a review on current findings - Behzad Einollahi; Mohsen Motalebi; Mahmood Salesi; Mehrdad Ebrahimi; Mehrdad Taghipour (Journal of Nephropathology, 2014)
Context: New onset diabetes mellitus after transplantation (NODAT) increases the risk of cardiovascular disease, rate of infections, graft rejection and graft loss as well as decreases patient and graft survival rates. There is a controversy surrounding the impact of cytomegalovirus (CMV) infection in the development of NODAT. This meta-analysis aims to identify the role of CMV infection leading to the development of NODAT in kidney recipient patients. Evidence Acquisitions: We searched several electronic databases, including PubMed, Embase, Medline, Scopus, Trip Database and Google Scholar for studies that completely fulfill our criteria between January 1990 and January 2014 Results: Seven studies with 1389 kidney transplant patients were included in this meta-analysis. The mean age of patients ranged from 42.8 to 48.8 years and males made up 53% to 75% of patients in the cohort studies. The incidence of NODAT varies from 14.3% to 27.1% in these studies. Overall adj OR was 1.94 [exp (0.66)] with a 95% CI of 1.26-2.98 [exp (0.23) and (1.09)]. There was no significant publication bias based on the Begg’s and Egger’s test (p value = 0.17 and 0.54, respectively). Conclusions: Our study showed that CMV infection is a risk factor for increasing incidence of NODAT. Thus, prophylaxis against CMV infection after kidney transplantation is strongly suggested. However, further clinical trials and cohorts are needed to confirm this association.